Lisensi paten - Budi Maulana, Insan; Indonesia (Bandung : Citra Aditya Bakti, 1996)
Patent laws and regulations, patent licenses, know-how assistance agreements; comments on article 78 of the Indonesian Patent Law; the need for implementary regulations.
"Undang-Undang Republik Indonesia nomor 6 tahun 1989 Tentang Paten": p. 95-146.
Includes bibliographical references (p. 87-94).
Keywords: Patent laws and legislation -- Indonesia; Licenses -- Indonesia